Role Of High Resolution Computed Tomogrpahy In Evaluation Of Temporal Bone In Middle And Innner Ear Pathology - Dr. Payal Parmar; Dr.Bharat Kumar Patel; Dr. Swati Mehta; Dr. Keval Kathiya; Dr. Bansari Dihora; Dr. Rajan Parmar; Dr. Mehandi Vadsaria (Global Journal of Medicine and Public Health, 2024)
Background: HRCT, a modification of routine CT, provides a direct visual window into the temporal bone providing minute structural details. Purpose of the present study is to evaluate the normal variations, pathological processes (infections, tumors and congenital anomalies) and their extent involving the temporal bone.